KEMAJUAN PT GUDANG GARAM TBK DALAM MENYUSUN BISNIS PLAN DAN MENINGKATKAN OPERASIONAL JARINGAN KERJA PERUSAHAAN - Nanda Ameliany (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
This study uses an object focus on Business Plan Analysis and Networks in Improving Business Operations at PT. Gudang Garam Tbk. With the form of the method used in this research is descriptive research. While the design used is a qualitative research design. The results of the research and data evaluation show that; Business Plan Implementation at PT. Gudang Garam Tbk has been implemented well and supports the improvement of its business operations. The network used has been effective in improving the business operations of PT. Gudang Garam Tbk. As well as the Business Plan and network have been implemented properly and the results are proven to improve business operations. PT. Gudang Garam Tbk in its business operations is designed in accordance with the expectations of the company and company stakeholders in achieving its goals so that business concepts and network formation are implemented as well as possible so that the company is able to operate optimally.